Análisis de las exportaciones del departamento de Caquetá durante el periodo 2011-2021 (2023)
The pourpose of this monograph was to analyze the behavior of exports in the department of Caqueta, specifically the behavior of the products exported by the department between 2011 and 2021. The monograph is developed under the format of an inductive study, whose information was obtained through primary and secondary sources. The proyect was structured around two central objectives that guided the research. The analysis of the behavior of exports in the department of Caqueta has presented a series of problems due to the fact that it has a low participation rate in terms of exports both nationally and internationally. The study was developed with the intention objective was to analyze them during the period 2011-2021.